Batida and the politics of sonic agency in Afro-Lisboa - Raposo, O.; Garrido Castellano, C. (Unwritten Afro-Iberian memories and histories: Race, ethnicity and gender in Portugal and Spain, 2026)
This chapter examines the politics of sonic agency in batida, the most successful recent electronic musical style emerging from Lisbon’s outskirts in Portugal. The genealogies of batida are closely linked to the emergence of a young generation of Djs do Gueto [Ghetto Djs] who unabashedly claim their right of belonging as major players within the Portuguese acoustic and cultural fields. We analyse batida as a space for agency and affirmative mobilisation of Afro-Portuguese populations. Two elements are of special interest: the digital recombination to celebrate the irreducibility of Afro-Portuguese experience, and the way in which racial exclusion, urban segregation, and racism are problematised through the act of inscribing the neighbouring sounds of peripheral neighbourhoods in their music. Through the examination of these two elements, we aim to position sonic agency as a central space in the configuration of racial politics and processes of nation building in the Portuguese case.